PERAN PSIKOLOGI GURU DALAM DINAMIKA KEMAJUAN SEKOLAH: STUDI KUALITATIF DI SMP 5 MUHAMMADIYAH NGAWI - Yusron Hanafi; Ndaru Putri Yudhiarti; Darmanto (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) STIT Muhammadiyah Tempurejo, Ngawi, Jawa Timur, 2026)
ABSTRACT Teacher psychology is a crucial factor in determining the dynamics of school progress, particularly in building a conducive learning climate, fostering healthy interpersonal relationships, and enhancing student motivation. This study aims to analyze the role of teacher psychology in promoting school progress at SMP 5 Muhammadiyah Ngawi. The study employed a qualitative approach with a case study design. Subjects included the principal, teachers, and students. Data collection techniques included in-depth interviews, participant observation, and documentation. Data analysis employed an interactive model encompassing data reduction, data presentation, and conclusion drawing. The results indicate that teachers' psychological well-being, such as motivation, emotional well-being, self-efficacy, and emotional regulation, play a significant role in improving the quality of learning and school culture. However, teachers also face psychological challenges in the form of workload and professional pressure. Therefore, leadership support and a supportive work environment are key to sustainable school progress.